Hepatitis B and E viral infection among Nigerian healthcare workers (2012)
"BACKGROUND:There is dearth of information on Hepatitis E virus (HEV) infection and its co-infection with HBV among Nigerian healthcare workers (HCWs). Hence, there is the need to determine the rate of HEV infection and its association with HBV among HCWs who are at greater risk of nosocomial infections. METHODOLOGY:Sera from 88 HCWs and 44 non-HCWs healthy adults as controls were tested for the presence of antibody to HEV (anti-HEV). The HCWs were also tested for HBsAg and antibody to Hepatitis B core antigen (anti-HBc) using commercially available ELISA kits. RESULTS:The prevalence of anti-HEV obtained among the HCWs and controls were 43% and 94% respectively (p<0.005) while those of HBsAg and anti-HBc in HCWs were respective 13% and 56%. Overall among HCWs, the prevalence of HBV infection was 65.9%, higher than HEV infection (p<0.005) with only anti-HBc greater among the male participants (p<0.005) while co-infection of HBV with HEV was 27.3%. HEV infection was least among the Paediatricians (18%) and highest among the Surgeons (55%) while HBV infection was similar in all the different occupational groups of HCWs (44-59%) except among the Gynecologists and Obstetricians (80%). CONCLUSION:Infection with HEV is high among Nigerian HCWs but lower than the rate among non-HCWs. It is also co-infected with HBV especially among the different groups of the HCWs and could occur with the diverse clinico-serological patterns of HBV infection."